2014
DOI: 10.1152/jn.00626.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unilateral deactivations of dorsolateral prefrontal cortex and anterior cingulate cortex on saccadic eye movements

Abstract: Koval MJ, Hutchison RM, Lomber SG, Everling S. Effects of unilateral deactivations of dorsolateral prefrontal cortex and anterior cingulate cortex on saccadic eye movements. J Neurophysiol 111: 787-803, 2014. First published November 27, 2013 doi:10.1152/jn.00626.2013.-The dorsolateral prefrontal cortex (dlPFC) and anterior cingulate cortex (ACC) have both been implicated in the cognitive control of saccadic eye movements by single neuron recording studies in nonhuman primates and functional imaging studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 145 publications
1
8
1
Order By: Relevance
“…Interestingly, in that study, both selection biases and RT changes were less pro-nounced following lesions of the SEF, similar to the differences in magnitude of both RT and selection biases between the DPC and cPS loops we observed here. Although our laboratory has previously reported decreases in saccade peak velocity and increases in saccade duration during unilateral dorsolateral PFC deactivation (Koval et al 2014), these changes are generally small, and we do not believe they contributed to the selection biases we observed here, since they reflect changes in motor output occurring after the initial selection process.…”
Section: Discussioncontrasting
confidence: 48%
“…Interestingly, in that study, both selection biases and RT changes were less pro-nounced following lesions of the SEF, similar to the differences in magnitude of both RT and selection biases between the DPC and cPS loops we observed here. Although our laboratory has previously reported decreases in saccade peak velocity and increases in saccade duration during unilateral dorsolateral PFC deactivation (Koval et al 2014), these changes are generally small, and we do not believe they contributed to the selection biases we observed here, since they reflect changes in motor output occurring after the initial selection process.…”
Section: Discussioncontrasting
confidence: 48%
“…The DLPFC has been frequently implicated in antisaccade execution although its specific role is still not fully understood (Johnston, Koval, Lomber, & Everling, 2014; Sweeney et al, 1996). It shows strong functional connectivity within the fronto-parietal network in resting state studies (Koval, Hutchison, Lomber, & Everling, 2014) projecting directly and indirectly to SC to mediate top-down resting and excitatory control over SC neurons (Johnston et al, 2014). Others have shown that components of the default mode network including the middle temporal gyrus and the inferior parietal cortex, as well as the parahippocampus, are also involved in active antisaccade generation (Domagalik et al, 2012; Talanow et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…5, Column 1]. A custom seed drawn to encompass the posterior end of the principal sulcus including area 46 and parts of 9/46 of the dorsal lateral PFC [Koval et al, 2014] showed a network of regions that resemble the macaque default-mode network [Hutchison and Everling, 2012;Hutchison et al, 2011;Mantini et al, 2011;Fig. 5, Column 2].…”
Section: Seed-based Analysismentioning
confidence: 99%